Identification of SMYD2 as a candidate diagnostic and prognostic biomarker for gastric cancer - Wang, Sichao; Zhao, Chuanxi; Li, Dongmei; Liu, Qingzhi; Mao, Cuiping; Ding, Shanshan; Zhang, Shujun; Shang, Wenjing (Frontiers in Oncology, 2025)
BackgroundHistone modification enzymes (HMEs) are associated with cancer development, treatment response, and prognosis. However, the potential roles of HMEs in gastric cancer (GC) remain unclear. This study aimed to investigate their biological functions and mechanisms in GC, with additional focus on exploring the clinical value of SMYD2.MethodsWe performed integrated analyses of transcriptome profiling and somatic mutation alteration in GC samples from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) datasets to characterize HMEs alterations in GC. Consensus unsupervised clustering analysis was performed to identify HMEs-associated GC subtypes. Various machine learning methods were employed to construct an HMEs-based diagnostic model for GC. The area under the receiver operating characteristic (ROC) curve (AUC) was used to evaluate model performance. SMYD2 expression in GC tissues was analyzed using TCGA and GEO data and validated by immunohistochemistry (IHC). The association between SMYD2 and the tumor immune microenvironment in GC was evaluated using CIBERSORT, ESTIMATE, and TIDE algorithms. Functional characterization of SMYD2 was performed via SMYD2 knockdown in GC cells.ResultsMost HMEs were up-regulated in GC tissues and exhibited relatively high mutation frequencies. GC patients were stratified into three HMEs-associated subtypes, with cluster 2 (C2) demonstrating significantly better prognosis than C1 and C3. The diagnostic model based on HMEs expression profiles showed robust performance for GC diagnosis. Notably, SMYD2 expression showed positive associations with CD8+ T cells, activated CD4+ T cells, and M0/M1 macrophages, but negative associations with M2 macrophages, regulatory T cells, stromal score, and TIDE score. Functional assays demonstrated that SMYD2 promoted GC cell proliferation, invasion, and migration in vitro.ConclusionsThese findings established SMYD2 is a major oncogene that can serve as a candidate diagnostic and prognostic biomarker for GC.